2021
DOI: 10.3390/diagnostics11030479
|View full text |Cite
|
Sign up to set email alerts
|

A New Gold Rush: A Review of Current and Developing Diagnostic Tools for Urinary Tract Infections

Abstract: Urinary tract infections (UTIs) are one of the most common infections in the United States and consequently are responsible for significant healthcare expenditure. The standard urine culture is the current gold standard for diagnosing urinary tract infections, however there are limitations of the test that directly contribute to increased healthcare costs. As a result, new and innovative techniques have been developed to address the inefficiencies of the current standard—it remains to be seen whether these tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…This approach has changed with the start of the Human Microbiome Project, the first large-scale mapping of the human microbiome using culture-independent methods. Standard urine cultures detect aerobic and fast-growing bacteria, while slow-growing anaerobic microorganisms or bacteria that require different growth conditions remain undetected [ 12 , 13 ].…”
Section: The Urobiome Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has changed with the start of the Human Microbiome Project, the first large-scale mapping of the human microbiome using culture-independent methods. Standard urine cultures detect aerobic and fast-growing bacteria, while slow-growing anaerobic microorganisms or bacteria that require different growth conditions remain undetected [ 12 , 13 ].…”
Section: The Urobiome Investigationmentioning
confidence: 99%
“…Relatively recently, due to advances in bacterial assessment, it has been shown that the bladder is not a sterile environment [ 12 ]. In particular, new diagnostic techniques such as PCR, expanded quantitative urine culture (EQUC), whole-genome sequencing (WGS), and next-generation sequencing (NGS) including 16S ribosomal RNA gene sequencing allowed the discovery of uncultured microorganisms and revealed the existence of a urinary microbiome [ 12 , 13 , 14 ].…”
Section: The Urobiome Investigationmentioning
confidence: 99%
“…With a 95% sensitivity and 85% specificity at growth thresholds as low as 10 2 CFU/mL, the standard urine culture with sensitivity has been the clinician gold standard for diagnosing UTIs [91]. Although a clinically validated diagnostic tool, standard urine culture with sensitivity is not without its limitations.…”
Section: Diagnostic Strategies For Urinary Tract Infections In Develo...mentioning
confidence: 99%
“…Although a clinically validated diagnostic tool, standard urine culture with sensitivity is not without its limitations. The current process takes 48 to 72 h to receive organism identification with associated susceptibility data, allowing for a longer than necessary course of a potentially ineffective or overly broad agent [22,91,92]. Additionally, there has been controversy over the growth threshold to define a clinically significant and positive urine culture.…”
Section: Diagnostic Strategies For Urinary Tract Infections In Develo...mentioning
confidence: 99%
See 1 more Smart Citation